2,2-Dibenzylhydrazin-1-ium chloride - Tayamon, Shahedeh; S. A. Ravoof, Thahira Begum; Mohamed Tahir, Mohamed Ibrahim; Crouse, Karen Anne; Tiekink, Edward R. T. (International Union of Crystallography, 2013)
In the title salt, C14H17N2 +·Cl-, the central N atom is pyramidal (sum of bond angles = 330.9°) and there is a near orthogonal relationship between the benzene rings [dihedral angle = 89.95 (10)°]. The crystal packing features N - H⋯Cl hydrogen bonds, which lead to a supramolecular undulating ribbon along the a axis comprising edge-shared eight-membered {⋯HNH⋯Cl}2 synthons. The chains are connected into layers in the ab plane by C - H⋯π interactions.